Hereditary muscular dystrophies - V. B. Doronin; O. B. Doronina (Бюллетень сибирской медицины)
Precise diagnostic of hereditary muscular diseases begins to change during recent years due to genetic achievements. Genetic defects discoveries typical for different clinical variants of muscular dystrophies give opportunity for creation of specific testsystems to verify the diagnosis. Determination of gene and protein causes of neuromuscular pathology however does not exclude initial clinical diagnostic which cost less and easier to find.